Divergence in leaf and cambium phenologies among three temperate tree species of different wood types with special reference to xylem hydraulics - Wang, Ai-Ying; Li, Si-Qi; Cui, Han-Xiao; Liu, Ya-Nan; Lu, Yi-Jun; Hao, Guang-You (Frontiers in Plant Science, 2025)
Leaf and cambium phenologies are both important aspects of tree environmental adaptation in temperate areas. Temperate tree species with non-porous, diffuse-porous and ring-porous woods diverge substantially in the strategy of coping with freezing-induced hydraulic dysfunction, which can be closely associated with the timing of both leaf phenology and xylogenesis. Nevertheless, we still know little about the potential differences in the intra-annual process of xylogenesis among species of the three functional groups as well as its association with leaf phenology. Here, we monitored leaf phenology and xylogenesis in a non-porous (Pinus), a diffuse-porous (Populus), and a ring-porous (Ulmus) temperate tree species in a common garden. The results showed clear divergences in leaf and cambium phenologies and their chronological orders among the three species. The two hardwood species exhibited earlier bud burst and leaf unfolding than the conifer. The cambial activity of the ring-porous species began earlier than the diffuse-porous species, although the leaf phenology of the diffuse-porous species was earlier. The conifer species showed the latest bud break but the initiation of cambium activity was the earliest, which can be attributed to its strong resistance to freezing-induced embolism in the tracheid-based xylem. The leaf phenology preceded the onset of cambial activity in the Populus species, which was permitted by the ability of diffuse-porous species in largely retaining the stem hydraulic function over the winter. In contrast, the Ulmus species with ring-porous wood had to restore its severely hampered stem hydraulic function by winter embolism before leaf flush. The results revealed that leaf and cambium phenologies are closely interconnected due to the coordination between xylem water transport and leaf water demand. These findings contribute to a better understanding of the divergent adaptive strategies of temperate trees with different wood types.